A carbon dot-based high-water content strong hydrogel and preparation method thereof
By using hydroquinone carbon dots in hydrogels to form a crosslinking network with sodium alginate and polyvinyl alcohol, the problem of insufficient mechanical properties of traditional hydrogels is solved, and the high strength, high toughness and high conductivity of hydrogels under high moisture content are achieved.
Patent Information
- Application Number
- CN202411363912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-28
AI Technical Summary
Traditional single network hydrogels are weak in mechanical properties, difficult to have high toughness and high strength at the same time, and are prone to uneven stress caused by fracture in high moisture content environments.
By using hydroquinone carbon dots as nanofillers, a crosslinking network is formed with sodium alginate and polyvinyl alcohol, the mechanical properties and electrical conductivity of the hydrogel are enhanced by utilizing the SP2 crystal nuclei and functional groups of the specific carbon dots.
The high fracture strength (13.47MPa) and high toughness (39.61MJ/m-3) of the hydrogel under high moisture content (≥80%) were achieved, while maintaining good conductivity (3.06S/m).
Smart Images

Figure CN119264469B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a carbon-dot-based high-water-content strong-tough hydrogel and a preparation method thereof. Background Art
[0002] Hydrogels are a class of three-dimensional (3D) networks formed by hydrophilic polymer chains embedded in a water-rich environment, with widely adjustable physical and chemical properties. Hydrogels are widely used in wearable electronics, soft robotics, tissue engineering, flexible electronics, biomedicine, solid electrolytes and other fields due to their unique conductivity, tissue-like softness, stimulus responsiveness and biocompatibility. In these fields, excellent mechanical properties are essential. However, traditional single-network hydrogels are often soft or brittle, lack energy dissipation mechanisms and are susceptible to stress concentration. Their mechanical properties and toughness are weak, and there is a conflict between the toughness and stiffness of hydrogels and the fatigue threshold and stiffness. Improving mechanical strength often leads to material hardening, making it difficult for hydrogels to have high toughness and high strength at the same time. This poor mechanical property greatly limits the application of such hydrogels. Recently, carbon dot-based high-water-content strong and tough hydrogels have been developed through strategies such as constructing double networks, organic-inorganic hybridization, densification, synergistic effects and directional freezing. The hydrogels constructed by these methods show better mechanical strength. The strategy of strengthening and toughening at the expense of hydrogel water content runs counter to the requirement of high water content of load-bearing tissue mimics (for example, cartilage has a water content of 65% to 80%); high water content gives hydrogels water retention and permeability, and provides essential nutrients for cell life activities, which is the prerequisite for biomedical applications such as load-bearing tissue replacement. However, it is difficult for carbon dot-based high-water-content hydrogel materials to achieve a fracture strength of 13.47MPa and a strength of 39.61MJ / m -3 (This is because the water content in the hydrogel is very high, which will weaken the interaction between the polymer chains and reduce the overall strength of the material. Since most of the volume in the hydrogel is water, the number of polymer chains that truly provide mechanical strength is limited, which limits its mechanical properties. Traditional hydrogels have a low cross-linking density, resulting in poor mechanical properties. Although increasing the cross-linking density can increase strength, it often sacrifices the toughness and ductility of the material. In a high water content environment, stress may not be evenly distributed inside the hydrogel, causing the material to break at lower stress). Therefore, it is necessary to prepare high-strength, high-toughness, and high-conductivity hydrogels under high water content (≥80%) conditions.
[0003] Nanofillers are materials with special properties. Their particle size is between 1 and 100 nm, including powdered or layered fillers (carbon nanotubes, graphene, and MXene, etc.). These nanoparticles exhibit surface effects, volume effects, quantum size effects, and macroscopic quantum tunneling effects due to their small size. They have attracted great attention due to the interfacial effect between them and polymers. However, the problem that comes with it is that nanofillers are prone to aggregation and agglomeration in the polymer matrix due to their high specific surface area and surface energy, resulting in uneven dispersion. This agglomeration will reduce the reinforcing effect of the filler and affect the mechanical properties of the composite material, thereby destroying the effectiveness of this strengthening strategy. Moreover, this interfacial interaction is usually based on weak physical effects and limited chemical bonding, and has limited improvement in the mechanical properties of the hydrogel. In addition, the poor compatibility between nanofillers and matrix materials may lead to insufficient interfacial bonding, affecting the overall performance of the material. Nanofillers are also expensive and cumbersome to prepare. Subsequently, carbon dots gradually came into people's view. Carbon dots (CDs) are carbon nanoparticles with a size of less than 10nm. As a new member of the "carbon family", carbon dots (CDs) quickly became a new type of carbon-based nanomaterials. In 2004, carbon nanoparticles with fluorescent properties were accidentally discovered during the purification of single-walled carbon nanotubes. In 2006, luminescent carbon was prepared by surface passivation. Due to its excellent optical properties, conductivity, low toxicity and high biocompatibility, this field has attracted many researchers. The introduction of carbon dots can not only improve the conductivity, but also enhance the mechanical properties of hydrogels, such as toughness and stretchability, which helps to maintain the integrity of the conductive network and further improve the conductivity. However, carbon dots are rarely used to improve the mechanical properties of composite materials. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a carbon dot-based high-water content strong and tough hydrogel and a preparation method thereof. The carbon dot-based high-water content strong and tough hydrogel of the present invention has a fracture strength of up to 13.47MPa and a toughness of up to 39.61MJ / m -3 , the conductivity can reach 3.06S / m.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A method for preparing a carbon dot-based high-water-content strong and tough hydrogel, which uses a hydroquinone carbon dot solution, sodium alginate and polyvinyl alcohol (PVA) as reactants, and obtains the carbon dot-based high-water-content strong and tough hydrogel through high-temperature reaction and freeze-thaw cycles.
[0008] Preferably, the preparation method of the hydroquinone carbon dot solution is: using hydroquinone as a raw material and water as a solvent, performing a hydrothermal reaction and cooling to obtain the hydroquinone carbon dot solution.
[0009] Preferably, in the method for preparing the hydroquinone carbon dot solution, the temperature of the hydrothermal reaction is 180° C. and the time is 1 hour.
[0010] Preferably, the concentration of the hydroquinone carbon dot solution is 0.5 wt %.
[0011] Preferably, the mass ratio of the hydroquinone carbon dot solution, sodium alginate and polyvinyl alcohol is (18-34):0.3:(1.7-5.7), more preferably 24:0.3:5.7, 34:0.3:5.7 or 18:0.3:1.7, and most preferably 24:0.3:5.7.
[0012] Preferably, in the method for preparing the carbon-dot-based high-water-content strong-tough hydrogel, the temperature of the high-temperature reaction is 90° C. and the time is 3 hours.
[0013] Preferably, in the method for preparing the carbon dot-based high-water-content tough hydrogel, the freeze-thaw cycle is freezing at -20°C for 8 hours, then thawing at 20°C for 3 hours, and the freeze-thaw cycle is repeated at least once.
[0014] In order to improve the mechanical properties of the hydrogel, the present invention designs specific carbon dots (hydroquinone carbon dots) as nanofillers, which are combined with the double network structure formed by sodium alginate and polyvinyl alcohol through hydrogen bonds. 2 The crystal nucleus can give the material good interface interactions (such as π-π stacking, CH-π, etc.), and after carbonization, the functional groups of the carbonized precursor can be well retained and have good dispersibility. In addition, the mechanical properties of the hydrogel are enhanced by non-covalent bonds between specific carbon points, polyvinyl alcohol and sodium ions, including π-π, CH-π, van der Waals force and ionic bonds.
[0015] The second technical solution of the present invention:
[0016] The present invention also provides a carbon dot-based high-water-content strong-tough hydrogel prepared according to the above preparation method, wherein the water content of the carbon dot-based high-water-content strong-tough hydrogel is ≥80%.
[0017] Preferably, the carbon-dot-based high-water-content strong hydrogel has a water content of 80-90%.
[0018] More preferably, the water content of the carbon-dot-based high-water-content strong hydrogel is 80%, 85% or 90%.
[0019] The carbon dot-based high-water-content strong-tough hydrogel of the present invention has a water content of 80-90% and a fracture strength of up to 13.47MPa and a toughness of up to 39.61MJ / m -3 , the conductivity can reach 3.06S / m. In summary, the present invention prepares a hydrogel with high strength, high toughness and high conductivity under the condition of high water content (≥80%).
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] The carbon dot-based high-water-content strong hydrogel of the present invention uses hydroquinone carbon dots as nanofillers to form a cross-linked network with sodium alginate and polyvinyl alcohol, and utilizes the intermolecular interaction between polyvinyl alcohol and sodium alginate and polyvinyl alcohol hydrogel to construct a high-water-content hydrogel with excellent mechanical properties.
[0022] The specific carbon dots (hydroquinone carbon dots) used in the present invention not only have attractive sp 2 The crystal nucleus can give the material good interface interaction (such as π-π stacking, CH-π, etc.), and the carbonized hydroquinone can well retain the functional groups of the carbonized precursor, has good dispersibility, and introduces a large number of physical cross-linking reaction sites for polyvinyl alcohol and sodium alginate hydrogel, which gives the hydrogel excellent fracture strength and toughness. The hydrogel preparation process of the present invention is simple and has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0024] Figure 1 The stress-strain curves of the hydrogels prepared in Example 1 and Comparative Example 1, Comparative Example 2 at a water content of 80% and different carbon dot concentrations (the carbon dot concentrations are 0.5wt%, 1wt% and 2wt%, respectively) and Comparative Example 3 at a water content of 80% and a hydroquinone solution concentration of 1wt%;
[0025] Figure 2 The stress-strain curves of the hydrogels prepared in Example 2, Comparative Example 4, and Comparative Example 5 at a water content of 85% and different carbon dot concentrations (the carbon dot concentrations are 0.5wt%, 1wt%, and 2wt%, respectively);
[0026] Figure 3 The stress-strain curves of the hydrogels prepared in Example 3, Comparative Example 6 and Comparative Example 7 at a water content of 90% and different carbon dot concentrations (the carbon dot concentrations are 0.5wt%, 1wt% and 2wt%, respectively);
[0027] Figure 4 is the stress-strain curve of the hydrogel prepared in Comparative Example 8 when the water content is 90%;
[0028] Figure 5 2. Nyquist plots of the hydrogels prepared in Example 1, Comparative Example 3 and Comparative Example 8. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0035] All raw materials and reagents used in the examples of the present invention are commercially available products.
[0036] In the present invention, the calculation method of the water content of the hydrogel is: water content of the hydrogel (%) = mass of the hydroquinone carbon dot solution or the mass of the hydroquinone solution ÷ (mass of the hydroquinone carbon dot solution or the mass of the hydroquinone solution + mass of the polyvinyl alcohol + mass of the sodium alginate) × 100%.
[0037] The technical solution of the present invention is further illustrated by the following embodiments.
[0038] Example 1
[0039] The preparation steps of hydroquinone carbon dot-based tough hydrogel with a water content of 80% and a concentration of 0.5wt% are as follows:
[0040] S1. Add 1 g of hydroquinone into 200 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 0.5 wt% hydroquinone carbon dot solution.
[0041] S2. The above-mentioned hydroquinone carbon dot solution (24 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (the freeze-thaw cycle was freezing at -20°C for 8 h, and then thawing at 20°C for 3 h, for a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 80%, that is, a carbon dot-based high water content strong hydrogel.
[0042] Example 2
[0043] The preparation steps of hydroquinone carbon dot-based tough hydrogel with a water content of 85% and a carbon dot concentration of 0.5wt% are as follows:
[0044] S1. Add 1 g of hydroquinone into 200 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 0.5 wt% hydroquinone carbon dot solution.
[0045] S2. The above-mentioned hydroquinone carbon dot solution (34 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (the freeze-thaw cycle was freezing at -20°C for 8 h, and then thawing at 20°C for 3 h, for a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 85%, that is, a carbon dot-based high water content strong hydrogel.
[0046] Example 3
[0047] The preparation steps of hydroquinone carbon dot-based tough hydrogel with a water content of 90% and a carbon dot concentration of 0.5wt% are as follows:
[0048] S1. Add 1 g of hydroquinone to 200 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 0.5 wt% hydroquinone carbon dot solution.
[0049] S2. The above-mentioned hydroquinone carbon dot solution (18 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (1.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (the freeze-thaw cycle was freezing at -20°C for 8 h, and then thawing at 20°C for 3 h, for a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 90%, that is, a carbon dot-based high water content strong hydrogel.
[0050] Comparative Example 1
[0051] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 80% and a concentration of 1wt% are as follows:
[0052] S1. Add 1 g of hydroquinone to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 1 wt% hydroquinone carbon dot solution.
[0053] S2. The above-mentioned hydroquinone carbon dot solution (24 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 80%.
[0054] Comparative Example 2
[0055] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 80% and a concentration of 2wt% are as follows:
[0056] S1. Add 2 g of hydroquinone to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 2 wt% hydroquinone carbon dot solution.
[0057] S2. The above-mentioned hydroquinone carbon dot solution (24 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 80%.
[0058] Comparative Example 3
[0059] The preparation steps of hydroquinone / sodium alginate / polyvinyl alcohol hydrogel with a water content of 80% and a concentration of 1wt% are as follows:
[0060] S1. Add 1 g of hydroquinone into 100 mL of deionized water and stir at room temperature for 2 h to obtain a hydroquinone solution;
[0061] S2. After mixing the above-mentioned hydroquinone solution (24 g) and sodium alginate (0.3 g), stir and react at room temperature for 2 hours, then add polyvinyl alcohol (5.7 g) and mix, react at 90°C for 3 hours, and after the reaction product is cooled to room temperature, perform freeze-thaw cycle treatment (freeze-thaw cycle is freezing at -20°C for 8 hours, then thawing at 20°C for 3 hours, a total of 3 freeze-thaw cycles) to obtain hydroquinone / sodium alginate / polyvinyl alcohol hydrogel.
[0062] Comparative Example 4
[0063] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 85% and a carbon dot concentration of 1wt% are as follows:
[0064] S1. Add 1 g of hydroquinone to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 1 wt% hydroquinone carbon dot solution.
[0065] S2. The above-mentioned hydroquinone carbon dot solution (34 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 85%.
[0066] Comparative Example 5
[0067] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 85% and a carbon dot concentration of 2wt% are as follows:
[0068] S1, add 2 g of the product into 100 mL of deionized water, place the product in a pressure-resistant reaction bottle, heat the solution to 180° C. and react for 1 h, and cool the reaction container naturally to room temperature to obtain a 2 wt% hydroquinone carbon dot solution;
[0069] S2. The above-mentioned hydroquinone carbon dot solution (34 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (5.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 85%.
[0070] Comparative Example 6
[0071] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 90% and a carbon dot concentration of 1wt% are as follows:
[0072] S1. Add 1 g of hydroquinone to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 1 wt% hydroquinone carbon dot solution.
[0073] S2. The above-mentioned hydroquinone carbon dot solution (18 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (1.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 90%.
[0074] Comparative Example 7
[0075] The preparation steps of hydroquinone carbon dot-based hydrogel with a water content of 90% and a carbon dot concentration of 2wt% are as follows:
[0076] S1. Add 2 g of hydroquinone to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 180° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a 2 wt% hydroquinone carbon dot solution.
[0077] S2. The above-mentioned hydroquinone carbon dot solution (18 g) and sodium alginate (0.3 g) were stirred at room temperature for 2 h, polyvinyl alcohol (1.7 g) was added and mixed, and the mixture was reacted at 90°C for 3 h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles) to obtain a hydroquinone carbon dot / sodium alginate / polyvinyl alcohol hydrogel with a water content of 90%.
[0078] Comparative Example 8
[0079] The preparation steps of polyvinyl alcohol hydrogel are as follows:
[0080] Polyvinyl alcohol (2 g) and deionized water (18 g) were mixed and reacted at 90°C for 3 h. After the reaction product was cooled to room temperature, a freeze-thaw cycle was performed (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, a total of 3 freeze-thaw cycles), to obtain a polyvinyl alcohol hydrogel, denoted as PVA. The calculation method of the water content of the hydrogel prepared in this comparative example is: hydrogel water content (%) = deionized water mass ÷ (deionized water mass + polyvinyl alcohol mass) × 100%.
[0081] The hydrogels prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to mechanical property testing and toughness calculation as follows:
[0082] The dumbbell-shaped (75 mm×12.5 mm×2 m) hydrogels prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to tensile property tests at room temperature. The uniaxial tensile test was performed using an electronic universal testing machine (Shenzhen Sun Technology Co., Ltd., China) at an extension speed of 80 mm / min.
[0083] Toughness is calculated based on the area under the stress-strain curve using the following formula:
[0084] △U=∫σds
[0085] Where σ and ε are the stress (MPa) and strain (%) of the hydrogel, respectively.
[0086] The conductivity of the hydrogels prepared in Example 1, Comparative Example 8 and Comparative Example 9 was tested and calculated as follows:
[0087] The electrochemical properties of the hydrogel were evaluated by an electrochemical workstation (model). The hydrogel samples were cut into strips of 40 (length) × 6 (width) × 2 mm (thickness). Electrochemical impedance spectroscopy (EIS) was used with a voltage of 0.1 V and a frequency range of 105 to 0.1 Hz. The conductivity was calculated by the following formula:
[0088]
[0089] Where L is the distance between adjacent electrodes (cm), R is the resistance of the hydrogel (Ω), and S is the contact area between the hydrogel and the electrode (cm 2 ).
[0090] The water content, breaking strength and toughness of the hydrogels prepared in Examples 1 to 3 and Comparative Examples 1 to 8 are shown in Tables 1 to 3.
[0091] Table 1
[0092] Test piece Moisture content (%) Breaking strength(MPa) <![CDATA[Toughness (MJ / m 3 )]]> Example 1 80 13.47 39.61 Comparative Example 1 80 8.44 19.3 Comparative Example 2 80 7.09 16.12 Comparative Example 3 80 7.9 21.82
[0093] Table 2
[0094] Test piece Moisture content (%) Breaking strength(MPa) <![CDATA[Toughness (MJ / m 3 )]]> Example 2 85 8.4 17.24 Comparative Example 4 85 4.48 10 Comparative Example 5 85 2.38 7.11
[0095] Table 3
[0096] Test piece Moisture content (%) Breaking strength(MPa) <![CDATA[Toughness (MJ / m 3 )]]> Example 3 90 2.8 3.7 Comparative Example 6 90 2.69 5.16 Comparative Example 7 90 1.63 4 Comparative Example 8 90 0.27 0.53
[0097] It can be seen from the data in Tables 1, 2 and 3 that the fracture strength and toughness of the hydrogel prepared in Example 1 are the largest, reaching 13.47 MPa and 39.61 MJ / m 3 From the data changes of comparative examples 1 to 8, it can be seen that the mechanical properties of hydroquinone carbon dots / sodium alginate / polyvinyl alcohol hydrogels are affected to a certain extent at different water contents and different carbon dot concentrations, indicating that the hydrogels prepared by the present invention using hydroquinone carbon dots as nanofillers of polyvinyl alcohol hydrogels at different water contents and different carbon dot concentrations have better mechanical properties.
[0098] Figure 1 The stress-strain curves of the hydrogels (water content of 80%) prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 show that the mechanical properties of the hydrogels prepared based on different carbon dot concentrations (0.5wt%, 1wt%, 2wt%) decrease from 13.47MPa to 7.09MPa. When the carbon dot concentration is 0.5wt%, the mechanical properties of the hydrogel are the strongest. Physical crosslinking points can be formed between the hydrogels to increase the stability of the network. When the carbon dot concentration is too high (>0.5wt%), a dense network structure may be formed, resulting in excessive crosslinking, and phase separation or aggregation may be caused, affecting the interaction between the molecular chains of sodium alginate and polyvinyl alcohol hydrogels, resulting in the inhomogeneity of the hydrogel, thereby weakening the overall mechanical properties of the hydrogel.
[0099] Figure 2The stress-strain curves of the hydrogels (water content 85%) prepared in Example 2, Comparative Example 4 and Comparative Example 5 show that the fracture strength and toughness of the hydrogels prepared based on different carbon dot concentrations (0.5wt%, 1wt%, 2wt%) are 8.4MPa, 4.48MPa, 2.38MPa and 17.24MJ / m, respectively. 3 、10MJ / m 3 and 7.11MJ / m 3 , because the preparation of hydroquinone carbon dots involves the chemical reaction of hydroquinone to generate carbon dots, which usually have good dispersibility and surface functionalization, and can form strong crosslinks with sodium alginate and polyvinyl alcohol. By constructing a double network strategy, the crystal morphology of the polymer network is finely controlled, and the fracture strength and toughness of the hydrogel are improved without sacrificing the water content. As the water content of the hydrogel increases, its crosslinking effect in the hydrogel is poor, thus affecting the mechanical properties and toughness.
[0100] Figure 3 The stress-strain curves of the hydrogels (water content 90%) prepared in Example 3, Comparative Example 6 and Comparative Example 7 show that the fracture strength and toughness of the hydrogels prepared based on different carbon dot concentrations (0.5wt%, 1wt%, 2wt%) are 2.8MPa, 2.69MPa, 1.63MPa and 3.7MJ / m, respectively. 3 5.16MJ / m 3 and 4MJ / m 3 , because the preparation of hydroquinone carbon dots involves the chemical reaction of hydroquinone to generate carbon dots, which usually have good dispersibility and surface functionalization, and can form strong crosslinks with sodium alginate and polyvinyl alcohol. By constructing a double network strategy, the crystal morphology of the polymer network is finely controlled, and the fracture strength and toughness of the hydrogel are improved without sacrificing the water content. As the water content of the hydrogel increases, its crosslinking effect in the hydrogel is poor, thus affecting the mechanical properties and toughness.
[0101] Figure 4 The stress-strain curve of the hydrogel (water content 90%) prepared in Comparative Example 8 shows that the mechanical properties (fracture strength and toughness) of the polyvinyl alcohol hydrogel are 0.27 MPa and 0.53 MJ / m 3 This is because polyvinyl alcohol hydrogel has a high water content, which makes it flexible and absorbent, but also reduces the mechanical strength of the material. The presence of water weakens the mechanical strength of the PVA chain, causing the hydrogel to deform and break easily under stretching or pressure.
[0102] Figure 5The Nyquist diagrams of Example 1, Comparative Example 3 and Comparative Example 8. The hydroquinone carbon dots / sodium alginate / polyvinyl alcohol hydrogel has high conductivity. The Nyquist diagram shows that the hydrogel has stable electrical properties. Its conductivity of 3.06S / m is different from the 1.26S / m of the hydroquinone / sodium alginate / polyvinyl alcohol (uncarbonized, Comparative Example 3) hydrogel and the 0.32S / m of the polyvinyl alcohol (Comparative Example 8) hydrogel. Since the surface of the hydroquinone carbon dots has abundant -OH functional groups, it can coordinate with metal ions to enhance the wettability between the electrode material and the electrolyte; since the hydroquinone carbon dots themselves have high electron mobility and good electron transport performance. When the hydroquinone carbon dots are dispersed in the sodium alginate / polyvinyl alcohol hydrogel double network, a conductive path can be formed to increase the migration rate of electrons; in addition, the carbon dots are usually at the nanometer level, and they show a quantum size effect, which can adjust their band structure and electronic properties, thereby further optimizing the conductive properties. Carbon dots can form a three-dimensional conductive network in hydrogels. This network structure helps to improve the efficiency of charge transfer and enhance the overall conductivity of hydrogels. Polyvinyl alcohol is a non-conductive polymer that does not contain freely moving charge carriers. Carbon and oxygen atoms mainly exist in the form of covalent bonds. The molecular structure is stable, which is not conducive to charge transfer and leads to low conductivity. The three-dimensional network structure of PVA hydrogel is composed of cross-linked PVA molecular chains. This structure limits the migration of charge carriers, thereby reducing conductivity.
[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a carbon-dot-based high-water-content strong hydrogel, characterized in that: Using hydroquinone carbon dot solution, sodium alginate and polyvinyl alcohol as reactants, high temperature reaction and freeze-thaw cycles are performed to obtain the carbon dot-based high water content strong hydrogel; The concentration of the hydroquinone carbon dot solution is 0.5 wt %.
2. The method for preparing the carbon dot-based high-water-content tough hydrogel according to claim 1, characterized in that: The preparation method of the hydroquinone carbon dot solution is: The hydroquinone carbon dot solution is obtained by using hydroquinone as a raw material and water as a solvent through hydrothermal reaction and cooling.
3. The method for preparing the carbon dot-based high-water-content tough hydrogel according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 180° C. and the time is 1 h.
4. The method for preparing the carbon dot-based high-water-content tough hydrogel according to claim 1, characterized in that: The mass ratio of the hydroquinone carbon dot solution, sodium alginate and polyvinyl alcohol is (18-34):0.3:(1.7-5.7).
5. The method for preparing the carbon dot-based high-water-content tough hydrogel according to claim 1, characterized in that: The temperature of the high temperature reaction is 90° C. and the time is 3 hours.
6. The method for preparing the carbon dot-based high-water-content tough hydrogel according to claim 1, characterized in that: The freeze-thaw cycle is freezing at -20°C for 8 hours, then thawing at 20°C for 3 hours, and the freeze-thaw cycle is repeated at least once.
7. A carbon dot-based high water content strong hydrogel, characterized in that: The carbon-dot-based high-water-content strong hydrogel prepared by the preparation method according to any one of claims 1 to 6 has a water content of ≥80%.
8. The carbon dot-based high water content tough hydrogel according to claim 7, characterized in that: The water content of the carbon point-based high-water-content strong hydrogel is 80-90%.
9. The carbon dot-based high water content tough hydrogel according to claim 8, characterized in that: The water content of the carbon dot-based high-water-content strong hydrogel is 80%, 85% or 90%.
Citation Information
Patent Citations
Preparation method, product and application of bio-electronic hydrogel
CN111363097A
Transparent conductive hydrogel with adhesion as well as preparation method and application of transparent conductive hydrogel
CN114149599A